Family Law Reimagined - Jill Elaine Hasday (Harvard University Press, 2014)
The law shapes all of our lives, even when we do not realize it is there. It decides who has rights to what, who can make enforceable claims on whom, who is entitled and who is not. Family life is sometimes presumed to be a realm so private and intimate as to be beyond the lawâ€™s power. Indeed, the United States Supreme Court itself has contributed to that notion, repeatedly declaring that there is a â€œprivate realm of family life which the state cannot enter.â€1 But in fact, one of the lawâ€™s most important and far- reaching roles is to govern family life and family members. Family law regulates the creation and dissolution of legally recognized family relationships and establishes the legal rights and responsibilities that are tied to family status. This means that family law decides who counts as kin in the eyes of the law and who does not, how family relationships are legally formed and severed, and what turns on legal recognition as a family memberâ€” what it means legally to be a spouse, parent, child, sibling, or other relative as one interacts with the government and with other people inside and outside of oneâ€™s family. Family law is extraordinarily consequential, whether measured in terms of impact on peopleâ€™s lives, volume of litigation, or monetary, psychological, and cultural goods at stake. Family law shapes social organization, economic status, intergenerational relationships, intimacy, childhood, maturity, and everyday experience. It reflects and influences how Americans think about gender, race, class, sexual orientation, and other divides and helps determine how those categories will impact peopleâ€™s opportunities, choices, rights, and constraints. Family law helps structure both the details of daily existence and the overarching features of society.